RANCANG BANGUN LAMPU OTOMATIS MENGGUNAKAN SENSOR CAHAYA BERBASIS ARDUINO DI POLRES PEMATANGSIANTAR - Dimas Bayu Rizki; Sumarno Sumarno; Muhammad Ridwan Lubis; Sundari Retno Andani; Ika Purnama Sari (Jurnal Ilmiah Sains dan Teknologi, 2022)
A Lights are one of the basic needs in everyday life, both in household life, offices, and others, especially at the Pematangsiantar Police Station. In line with the rapid development in the field of technology, the amount of electricity demand tends to increase rapidly. This increase in demand can be caused by the increasing number of people using electrical technology. However, there needs to be a wise attitude in the use of this lighting energy source. If the lamp is left on, it will waste electricity. This often happens because you forget to turn it off. But if it is turned off then at night it will be dark until someone turns on the light. Therefore, automation is needed in regulating the use of electrical energy in lamps. In this case, an automatic lamp design was made using an Arduino-based light sensor that can be set to turn on and off automatically according to the intensity of sunlight received so that it will suit the needs of the lamp. This automatic lamp is equipped with Arduino, LDR module, and relay. The lighting load is usually operated manually by humans, with this study, human intervention in operations can be reduced. The results of this study showed that the Arduino-based light sensor can be implemented in the design of automatic lights. Keyword: Design, Automatic Lights, Light Sensors, Arduino, Polres Pematangsiantar